Preparation method, material and application of gold and cobalt nanoparticle anchored nitrogen-doped carbon nanosheet array three-dimensional graphene foam composite material
By preparing a three-dimensional graphene foam composite material with nitrogen-doped carbon nanosheet array anchored by gold and cobalt nanoparticles, the problems of low sensitivity and poor stability in detecting levodopa blood drug concentration are solved, and high sensitivity is achieved and the detection effect of low detection limit.
Patent Information
- Application Number
- CN202411498661.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-02-18
AI Technical Summary
Existing materials have low sensitivity, poor stability and high detection limits when detecting levodopa blood drug concentration, making it difficult to meet the needs of rapid clinical testing.
The composite material was prepared by room temperature synthesis, heat treatment and self-assembly steps using a three-dimensional graphene foam composite with a nitrogen-doped carbon nanosheet array anchored as the electrode material.
The sensitivity to detect levodopa concentration is significantly improved, the detection limit is reduced to 0.02μM, and the material stability and electrochemical performance are excellent.
Smart Images

Figure HDA0005101971840000011 
Figure HDA0005101971840000012 
Figure HDA0005101971840000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of novel nano functional materials and electrochemical biosensor detection, and discloses a preparation method of a gold and cobalt nanoparticle anchored nitrogen-doped carbon nanosheet array three-dimensional graphene foam composite material, the material and the use of the composite material. Background Art
[0002] Parkinson's disease (PD) is the second largest neurodegenerative disease. The prevalence rate in people over 65 years old in my country is about 1%, and the prevalence rate in people over 80 years old is more than 4%. It is predicted that by 2030, the number of PD patients in my country will reach 4.94 million, accounting for half of the world's PD patients. Levodopa (LD) is the gold standard drug for the treatment of PD. However, with the progression of the disease and the long-term use of LD, LD-induced dyskinesia is a common disabling drug complication that seriously affects the quality of life of patients. After 10 years of LD treatment, the incidence of dyskinesia is as high as 90%.
[0003] Although the occurrence of dyskinesia is related to the age of onset, gender, weight, and severity of the disease, LD concentration is still the most important influencing factor. According to the relationship with LD blood concentration, dyskinesia is divided into peak dyskinesia (occurring when LD blood concentration reaches a peak), biphasic dyskinesia (occurring when LD blood concentration rises or falls), and off-phase dystonia (occurring when LD blood concentration is low). The Chinese Parkinson's Disease Treatment Guidelines propose corresponding drug adjustment plans for the above different types of dyskinesia. At present, doctors only rely on medical history inquiries to guess the type of dyskinesia based on clinical manifestations, the relationship between the time of dyskinesia onset and the time of oral LD, and the half-life of LD. However, due to different responses of patients to LD treatment, the time when LD blood concentration reaches the peak varies greatly from person to person. Even for the same individual, the change pattern of LD blood concentration is still variable in different dosing cycles. Moreover, as the disease progresses, the therapeutic window of LD gradually narrows. The above factors make it more complicated to judge the type of dyskinesia. Doctors often misjudge the type of dyskinesia based on clinical experience alone. Therefore, a key point in treatment is to detect the LD blood concentration at consecutive time points during the dosing cycle and establish its relationship with time, and accurately classify the dyskinesia based on the LD blood concentration when the dyskinesia occurs.
[0004] Currently, the "gold standard" for detecting LD concentration relies on liquid chromatography-mass spectrometry analysis of plasma samples. Due to the need for specialized instruments and personnel, high cost, and long turnaround time, this method is only suitable for research testing. Therefore, there is an urgent need for a method that can quickly detect LD blood concentration for drug analysis and clinical application.
[0005] Electrochemical methods are widely used in the determination of levodopa due to their high sensitivity, strong selectivity and high accuracy. Nevertheless, the detection limit of this method is still large, and the sensitivity and selectivity are still poor. Currently, the development of new electrode materials is key to improving the performance of electrochemical methods. Summary of the invention
[0006] In order to solve the problems of low sensitivity, poor stability and high detection limit of existing materials when detecting the blood concentration of levodopa, the present invention provides a preparation method of a three-dimensional graphene foam composite material of gold and cobalt nanoparticles anchored with nitrogen-doped carbon nanosheet arrays, a composite material and uses of the composite material. A new three-dimensional graphene foam composite material of gold and cobalt nanoparticles anchored with nitrogen-doped carbon nanosheet arrays can be prepared by the method of the present invention. The composite material has high sensitivity and low detection limit for detecting the concentration of levodopa.
[0007] In a first aspect, the present invention provides a method for preparing a three-dimensional graphene foam composite material of gold and cobalt nanoparticles anchored with nitrogen-doped carbon nanosheet arrays, comprising the following steps: (1) placing a three-dimensional graphene foam subjected to surface oxidation treatment in a mixed solution of cobalt nitrate hexahydrate and dimethylimidazole, and maintaining the mixture at room temperature for 2-12 hours; washing the obtained product with deionized water and drying it to obtain dimethylimidazole cobalt (ZIF-67) nanosheet array / three-dimensional graphene foam; wherein the size of the three-dimensional graphene foam is 2×2 cm 2 , and in the mixed solution, the concentration of cobalt nitrate hexahydrate is 0.0006mol / L to 0.1mol / L, and the concentration of dimethylimidazole is 0.0006mol / L to 0.1mol / L; (2) heat treating the ZIF-67 nanosheet array / three-dimensional graphene foam at 300℃-900℃ in an argon atmosphere for 1-5h; then cooling to room temperature to obtain cobalt nanoparticle-anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam; (3) measuring 5-50μL of a carboxyl-containing gold nanoparticle solution, and dripping it on the surface of the cobalt nanoparticle-anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam; then maintaining it at 25℃-80℃ for 2-12h for self-assembly to obtain gold and cobalt nanoparticle-anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam.
[0008] In the method of the present invention, in step (1), the "mixed solution of cobalt nitrate hexahydrate and dimethylimidazole" means a mixed solution obtained by dissolving cobalt nitrate hexahydrate and dimethylimidazole in deionized water; in the method of the present invention, in step (1), the cobalt nitrate hexahydrate and the dimethylimidazole in deionized water can be stirred and mixed for 20-40 minutes, for example, 30 minutes; in the method of the present invention, in step (1), the room temperature is 25°C-80°C.
[0009] In the method of the present invention, in step (1), in the mixed solution, the concentration of cobalt nitrate hexahydrate is 0.001 mol / L to 0.05 mol / L, the concentration of dimethylimidazole is 0.001 mol / L to 0.05 mol / L, preferably 0.01 mol / L to 0.05 mol / L, more preferably 0.02 mol / L to 0.03 mol / L, for example 0.025 mol / L, and all values therebetween and including all ranges obtained by selecting any lower limit value and combining with any upper limit value.
[0010] In the method of the present invention, in step (1), the three-dimensional graphene foam is placed in a mixed solution of cobalt nitrate hexahydrate and dimethylimidazole and maintained at room temperature for 3h-9h, preferably 5h-8h, and more preferably 6h. The holding time at room temperature can also be all values between any lower limit value and any upper limit value listed, as well as all values in all ranges obtained by selecting any lower limit value and combining it with any upper limit value.
[0011] In the method of the present invention, in step (2), the ZIF-67 nanosheet array / three-dimensional graphene foam can be placed in a container and heat treated in an argon atmosphere at a temperature of 500°C-800°C, preferably 700°C. The heat treatment temperature can also be all values between any lower limit value and any upper limit value listed, as well as all values in all ranges obtained by selecting any lower limit value and combining it with any upper limit value; wherein the container is selected from an alumina ceramic boat, but is not limited thereto.
[0012] In the method of the present invention, in step (2), the heat treatment time is 1h-3h, for example 2h. The heat treatment time can also be all values between any lower limit value and any upper limit value listed, as well as all values in all ranges obtained by selecting any lower limit value and combining it with any upper limit value.
[0013] In the method of the present invention, in step (3), the solution of gold nanoparticles with carboxyl groups can be measured with a pipette.
[0014] In the method of the present invention, in step (3), 5 μL-30 μL, preferably 5 μL-20 μL, more preferably 5 μL-15 μL, for example 10 μL, of a carboxyl-carrying gold nanoparticle solution is measured and dripped onto the surface of the cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam. The amount of the carboxyl-carrying gold nanoparticle solution measured can also be all values between any lower limit and any upper limit listed, as well as all ranges of values obtained by selecting any lower limit and combining with any upper limit.
[0015] In the method of the present invention, in step (3), self-assembly is carried out at a temperature of 25°C-50°C, preferably 25°C-30°C. The temperature of self-assembly can also be all values between any lower limit value and any upper limit value listed, as well as all ranges of values obtained by selecting any lower limit value and combining it with any upper limit value.
[0016] In the method of the present invention, in step (3), self-assembly is carried out for 2h-8h, preferably 2h-6h, for example 4h. The time for self-assembly can also be all values between any lower limit value and any upper limit value listed, as well as all ranges of values obtained by selecting any lower limit value and combining it with any upper limit value.
[0017] In the method of the present invention, step (1) is to grow a ZIF-67 nanosheet array on a three-dimensional graphene foam prepared by a chemical vapor deposition method using a room temperature synthesis method; step (2) is to transform the ZIF-67 nanosheet array / three-dimensional graphene foam into a cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet array / three-dimensional graphene foam using a high-temperature calcination method; and step (3) is to self-assemble gold nanoparticles with carboxyl functional groups on the cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet array / three-dimensional graphene foam to obtain a three-dimensional graphene foam composite material of gold and cobalt nanoparticles anchored nitrogen-doped carbon nanosheet array.
[0018] In the method of the present invention, the three-dimensional graphene foam treated with surface oxidation is obtained by immersing the three-dimensional graphene foam in a mixed solution of concentrated hydrochloric acid and nitric acid (volume ratio of 1:3) at room temperature for 12 hours to oxidize the surface of the three-dimensional graphene foam.
[0019] In a second aspect, the present invention provides a three-dimensional graphene foam composite material of gold and cobalt nanoparticles anchored with nitrogen-doped carbon nanosheet arrays prepared according to the method of the present invention, wherein the composite material is composed of C, N, Co, Au and O elements, and has a morphology of triangular dimethylimidazole cobalt nanosheet arrays uniformly grown on oxidized three-dimensional graphene foam.
[0020] In a third aspect, the present invention provides a use of a three-dimensional graphene foam composite material of gold and cobalt nanoparticles anchored with nitrogen-doped carbon nanosheet arrays prepared according to the method of the present invention as an electrode material.
[0021] In a further embodiment of the use of the present invention, the composite material is used as an electrode for detecting the concentration of levodopa.
[0022] In yet a further embodiment of the use of the present invention, the composite material is used as an electrode for detecting the blood concentration of levodopa.
[0023] In yet a further embodiment of the use of the present invention, the composite material is used as an electrode to constitute an electrochemical detection instrument for detecting the blood concentration of levodopa.
[0024] The method of the present invention has the following beneficial effects:
[0025] (1) The method of the present invention utilizes cobalt ions and dimethylimidazole to form a dimethylimidazole cobalt (ZIF-67) nanosheet array structure, and uses the metal cobalt metal organic framework (MOF) array structure as a template to derive at high temperature to gold and cobalt nanoparticles anchoring nitrogen-doped carbon nanosheets. The method of the present invention self-assembles gold nanoparticles on the nitrogen-doped carbon nanosheet array derived from ZIF-67, and uniformly grows them on three-dimensional graphene foam, making full use of the high porosity and stability of the ZIF-67 nanosheet array, and synergizing with gold nanoparticles with high conductivity and high catalytic activity, and three-dimensional graphene foam, significantly improving the electrochemical performance of the product composite material when used in electrochemical sensors.
[0026] Three-dimensional graphene foam composites of gold and cobalt nanoparticles anchored with nitrogen-doped carbon nanosheet arrays can detect L-dopa with excellent sensitivity of 1.56 μA·μM-1·cm -2 (0-60 μM), or with higher sensitivity. The detection limit is 0.02 μM according to the calculation formula: LOD = S × 3 / σ, where σ is the standard deviation of the blank sample and S is the slope of the response curve.
[0027] (2) The method of the present invention specifically sets the concentrations of cobalt nitrate hexahydrate and dimethylimidazole in step (1) and the reaction time at room temperature, the temperature and insulation time of the heat treatment in step (2), and the amount of gold nanoparticle solution used in step (3) as well as the reaction temperature and time. The control conditions in the above three steps will affect the structure of the composite material, for example, the thickness and distribution uniformity of the ZIF-67 nanosheet array structure, and thus the electrochemical performance of the electrode using the composite material.
[0028] The present invention prepares a three-dimensional metal cobalt MOF array structure by oxidizing the surface of a three-dimensional graphene foam and conducting in-depth research on the concentration and reaction time of a MOF synthesis solution. That is, a nitrogen-doped carbon nanosheet array structure (such as a carbon nanosheet array) derived from a metal cobalt MOF is prepared on the surface of a three-dimensional graphene foam. Figure 1 This overcomes the problem that the existing preparation method of metal cobalt MOF often has a two-dimensional structure and the electrochemical performance of the composite material is poor.
[0029] (3) The process of the present invention is simple and environmentally friendly, and the yield of the three-dimensional graphene foam composite material of gold and cobalt nanoparticles anchored with nitrogen-doped carbon nanosheet arrays is high.
[0030] (4) In the three-dimensional graphene foam composite material of gold and cobalt nanoparticles anchored nitrogen-doped carbon nanosheet arrays prepared by the present invention, the three-dimensional graphene foam prepared by chemical vapor deposition can provide a highly conductive interconnected network with large porosity and high specific surface area; the ZIF-67 nanosheet array is beneficial to shortening the electron transmission path and increasing the contact area with the solution. The present invention can convert the ZIF-67 nanosheet array into a nitrogen-doped carbon nanosheet array anchored by cobalt nanoparticles through heat treatment, thereby improving the conductivity; gold nanoparticles have good conductivity, high active surface energy and excellent catalytic ability. The good biocompatibility and adsorption properties of gold nanoparticles are beneficial to capturing biological molecules and improving the reaction activity of the electrode surface.
[0031] (5) The three-dimensional graphene foam composite material of gold and cobalt nanoparticles anchored with nitrogen-doped carbon nanosheet arrays prepared by the method of the present invention is a new composite material that has not been seen in the prior art. The composite material of the present invention is used as an electrode material of an electrochemical sensor for the electrochemical determination of levodopa and has good application prospects.
[0032] (6) Levodopa (LD) is the gold standard drug for the treatment of Parkinson's disease (PD), and dyskinesia is a common disabling complication of this drug. The occurrence of dyskinesia is closely related to the LD concentration, and there is an urgent need for a method to quickly detect the LD concentration in clinical practice, but there is a lack of such a method. The composite material electrode prepared by the method of the present invention and / or a device mainly comprising the composite material electrode is used to detect the LD concentration, which can simply and sensitively determine the relationship between the LD concentration and the time of medication, clinical symptoms and the occurrence of dyskinesia, assist doctors in accurately classifying dyskinesia, formulate individualized treatment plans for PD patients, and achieve precision treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The results were obtained using a scanning electron microscope (Apreo C) ( Figure 1 a-1j) and transmission electron microscope (FEI Talos F200x) ( Figure 1 k-1l) Characterization of the morphology of the three-dimensional graphene foam (Au@Co-NC NSAs / 3D GF) of gold and cobalt nanoparticles anchored nitrogen-doped carbon nanosheet arrays prepared by the method of Example 1.
[0034] Figure 2 The spectrum of the Au@Co-NC NSAs / 3D GF structure prepared by the method of Example 1 was characterized by X-ray diffraction (Cu Ka, Philips X′pert) and Raman spectroscopy (Horiba Scientific). The surface element types and valence states of Au@Co-NC NSAs / 3D GF were analyzed by X-ray photoelectron spectroscopy (PHI-5000versaprobeIII).
[0035] Figure 3 The electrochemical response of the Au@Co-NC NSAs / 3DGF electrode prepared by the method of Example 1 in LD solution and mixed UA or AA solution was shown by differential pulse voltammetry.
[0036] Figure 4 This is the result of the sensitivity of detecting LD using the composite material synthesized by the method of Example 2 as an electrode material.
[0037] Figure 5 This is a scanning electron microscope image of the gold and cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam composite material prepared in Comparative Example 1.
[0038] Figure 6 This is the result of the sensitivity of detecting LD using the composite material synthesized by the method of Comparative Example 1 as an electrode material.
[0039] Figure 7 This is a scanning electron microscope image of the gold and cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam composite material prepared in Comparative Example 2.
[0040] Figure 8 This is the result of the sensitivity of detecting LD using the composite material synthesized by the method of Comparative Example 2 as an electrode material.
[0041] Fig. 9 This is a scanning electron microscope image of the gold and cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam composite material prepared in Comparative Example 3.
[0042] Fig.10 This is the result of the sensitivity of detecting LD using the composite material synthesized by the method of Comparative Example 3 as an electrode material. DETAILED DESCRIPTION
[0043] raw material
[0044] Co(NO3)2·6H2O, dimethylimidazole (2-MIM), sulfuric acid, nitric acid, and hydrochloric acid were purchased from Tianli Chemical Company;
[0045] Argon (Ar) was purchased from Harbin Liming Company;
[0046] Ascorbic acid (AA), luteolin (LU), uric acid (UA), ITO glass, sulfuric acid, nitric acid, and phosphate buffer solution (PBS) were all analytically pure and purchased;
[0047] Gold nanoparticles with carboxyl groups (the surface of gold nanoparticles contains hydroxyl functional groups) with a particle size of 10 nm were purchased.
[0048] The three-dimensional graphene foam was prepared by the laboratory. The nickel foam (pore size 0.1 mm, porosity 98%) purchased from Kunshan Jiayisheng Electronics Co., Ltd. was prepared at a high temperature of 1000°C by passing methane, hydrogen and argon at flow rates of 20 Sccm, 200 Sccm and 500 Sccm respectively.
[0049] Example 1
[0050] (1) Preparation of ZIF-67 nanosheet arrays / 3D graphene foam by room temperature synthesis
[0051] 2mmol of cobalt nitrate hexahydrate and 2mmol of dimethylimidazole were added to 80mL of deionized water; stirred for 30min to obtain a mixed solution; then a piece of 2×2cm 2 The surface-oxidized three-dimensional graphene foam is placed in the mixed solution and maintained at 25° C. for 6 hours; the obtained product is washed with deionized water for 6 times and dried to obtain ZIF-67 nanosheet array / three-dimensional graphene foam;
[0052] (2) Preparation of cobalt nanoparticle-anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam by high-temperature calcination
[0053] The ZIF-67 nanosheet array / three-dimensional graphene foam was placed in an alumina ceramic boat and heat treated at 700° C. in an argon atmosphere for 2 h. The mixture was then cooled to room temperature to obtain cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam.
[0054] (3) Preparation of gold and cobalt nanoparticle-anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam by self-assembly
[0055] 10 μL of the gold nanoparticle solution with carboxyl groups was measured with a pipette and dropped onto the surface of the cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam, and kept at 25° C. for 4 h for self-assembly to obtain gold and cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam.
[0056] Each stage of the preparation process of Example 1 was characterized. Figure 1 As shown in (a), Au@Co-NC NSAs / 3DGF consists of an interconnected network with a pore size of approximately 100 μm, similar to that of three-dimensional graphene foam (3D GF). Figure 1 As shown in (b), triangular cobalt dimethylimidazole nanosheet arrays (ZIF-67NSAs) are uniformly grown on the oxidized 3D GF. After annealing at 700 °C, ZIF-67NSAs transform into Co-NC NSAs on 3D GF, presenting a cross-linked nanosheet array, as shown in Figure 2. Figure 1 (c) and Figure 1As shown in (d), due to the carbonization and shrinkage of ZIF-67NSAs, many pores are formed and Co nanoparticles appear on the surface of nanosheets, such as Figure 1 (e) Au@Co-NC NSAs / 3D GF is composed of C, N, Co, Au and O elements, which are evenly distributed according to the X-ray energy dispersive spectroscopy (EDS) results. Figure 1 (f)-1(j). Figure 1 The high-resolution transmission electron microscopy (HRTEM) image in (k) shows that Au nanoparticles (Au NPs) and Co nanoparticles (Co NPs) are distributed on the surface of the nanosheets. The crystal spacing of 0.10 and 0.14 nm is assigned to the (100) and (220) of Au NPs. The lattice fringes with spacing of 0.12 and 0.17 nm are completely consistent with the (220) and (200) of Co NPs, respectively. The lattice spacing of 0.21 and 0.34 nm corresponds to the (100) and (002) crystal planes of graphitic carbon, respectively. Figure 1 As shown in (l), four diffraction rings of different radii can be observed in the selected area electron diffraction (SAED) spectrum. The (004) that appears corresponds to graphite carbon, and the three diffraction rings from the inside to the outside correspond to the (100), (220) and (311) of Co nanoparticles. Due to the low content of Au nanoparticles, no diffraction rings were observed.
[0057] XRD characterization was performed on each stage of the preparation process of Example 1. Figure 2 As shown in (a), for ZIF-67NSAs / 3D GF, the characteristic peaks of ZIF-67 are located at 5-30°, which is consistent with the simulation results. The peaks at 26.2° and 43.1° correspond to the (200) and (100) of carbon in 3D GF, respectively. For Au@Co-NC NSAs / 3D GF, the peaks at 26.2° and 43.1° are significantly increased, indicating that the Co species in ZIF-67 has catalytic activity in converting amorphous carbon into graphitized carbon. In addition, the peak at 51.5° corresponds to the (200) crystal plane of Co. Figure 2 (b) 1577cm -1 The G peak at corresponds to the sp 2 The peak of the hybrid in-plane stretching movement is offset from the peak of pure graphite, which may be caused by the doping of N atoms. The disappearance of the D peak indicates that there are fewer impurities. -1 A 2D peak representing two photonic lattice vibration modes is observed at I 2D / I G is 0.5, indicating that the carbon material has a multilayer structure. Figure 2As shown in (c), in the XPS full spectrum, five characteristic peaks can be observed at 781eV, 532eV, 399eV, 285eV and 89eV, corresponding to Co 2p, O 1s, N 1s, C 1s and Au 4f, respectively. Four peaks are observed in the Co 2p spectrum, and the characteristic peaks at 780.8 and 796.6eV correspond to Co 2+ , while the characteristic peaks at 786.4 and 802.1 eV correspond to Co 3+ ,like Figure 2 In the O1s spectrum, two characteristic peaks were obtained by fitting, corresponding to the C=O (530.5 eV) and C-OH (531.6 eV) bonds, respectively. Figure 2 (e) In the N1s spectrum, the peaks at 399.7 and 401.7 eV are pyrrolic nitrogen and graphitic nitrogen, respectively, indicating the presence of nitrogen doping in the material, as shown in Figure 2 (f) As shown in the C1s spectrum, the peaks at 284.8, 285.9, 289.4, 293.1 and 295.8 eV are satellite peaks of CC, CO, C=O bond and C1s, respectively. Figure 2 (g) The Au 4f spectrum shows two different peaks, corresponding to Au 4f 5 / 2 and 4f 7 / 2 , indicating the existence of 0-valent and 2-valent Au, such as Figure 2 (h) All the results confirmed the successful synthesis of Au@Co-NC NSAs / 3D GF.
[0058] The composite material (block) prepared in Example 1 was directly used as an electrode material to form an electrode for detecting the concentration of LD in a solution. The results are as follows: Figure 3 shown.
[0059] like Figure 3 As shown in (a), the composite electrode was inserted into the LD solution, and it was found that with the increase of LD concentration, the oxidation peak current (located near 0.12V) increased. The linear fitting curve of the oxidation peak current value and LD concentration is I LD =(8.14±0.92)+(1.56±0.05)C LD (R 2 =0.9962), such as Figure 3 (b) This shows that the sensitivity of Au@Co-NC NSAs / 3D GF electrode in detecting LD is 1.56 μA·μM -1 cm -2 (0~60μM), the calculated LOD is 0.02μM.
[0060] In addition, the composite electrode was inserted into a mixed solution of LD and uric acid (UA). It was found that with the increase of LD concentration, the UA oxidation peak (at 0.26V) remained basically unchanged, while the LD oxidation peak (at 0.12V) increased, as shown in Figure 2. Figure 3 (c) and the linear relationship (I LD =(21.55±3.78)+(1.52±0.13)C LD , R 2 =0.9509) indicates a sensitivity of 1.52μA·μM -1 cm -2 ,like Figure 3 (d) as shown.
[0061] In addition, when the composite electrode was inserted into a mixed solution of LD and ascorbic acid (AA), two oxidation peaks were found near -0.05 and 0.12 V, corresponding to AA and LD, respectively. Figure 3 As shown in (e), with the increase of LD concentration, the LD oxidation peak increases, and the AA oxidation peak current at -0.05V remains basically unchanged. LD =(8.95±0.48)+(1.5±0.08)C LD (R 2 =0.9975), it can be seen that the sensitivity of Au@Co-NC NSAs / 3D GF electrode is 1.50μA·μM -1 cm -2 ,like Figure 3 As shown in (f), the Au@Co-NC NSAs / 3D GF electrode demonstrates good selectivity.
[0062] from Figure 3 The results show that the composite material electrode prepared in Example 1 exhibits excellent LD selectivity in different solutions containing LD. It can be inferred that the instrument composed of the electrode, such as a portable detector, also has excellent selectivity and stability when used for detecting LD blood concentration in patients.
[0063] 2-4 mL of venous blood was drawn from the subjects, and the blood samples were centrifuged at 3000 rpm for 5 minutes to prepare peripheral blood serum. The prepared serum was diluted in PBS and measured by electrochemical differential pulse voltammetry using a three-dimensional graphene foam composite electrode with gold and cobalt nanoparticles anchored with nitrogen-doped carbon nanosheet arrays, and the test results were compared with the results of existing high-performance liquid chromatography tests.
[0064] The gold and cobalt nanoparticles anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam composite electrode of Example 1 was used for the patient, and the LD blood concentration was detected by electrochemical method, so as to achieve accurate treatment of PD patients and avoid the occurrence of dyskinesia. Here is a clinical example for explanation: Patient basic information: male, 65 years old, weight 67kg, diagnosed with PD 15 years ago due to bradykinesia and right limb tremor, education level: high school, MMSE score: 27 points, UPDRS opening score: Part III 14 points, Part IV 11 points, Hoehn-Yahr stage: 3, medication status: After the diagnosis of PD, the initial oral administration of Madopar (each tablet contains 200mg levodopa and 50mg benserazide) had a good therapeutic effect (the specific dosage is unknown). Five years ago, the patient felt that the duration of the drug effect was shortened, and involuntary twisting of the neck and limbs occurred after taking the medicine, and dyskinesia was diagnosed. Currently, the patient takes 0.75 tablets of Madopar orally each time, 4 times a day. The patient felt that dyskinesia occurred more than 1 hour after oral medication, and lasted for about 1 hour to relieve. Before detecting the LD concentration, according to the time of dyskinesia and the time of oral medication, the patient was considered to have peak dyskinesia, and tried to reduce the dosage each time or increase the interval between medications, but the dyskinesia did not improve significantly. The patient was tested for LD blood concentration by electrochemical method using the new electrode material of the gold and cobalt nanoparticle anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam composite material of the present invention, which showed that the LD blood concentration reached a peak about 2 hours after taking the medication. The patient developed dyskinesia half an hour after oral medication, and the UDysRS (16-26 items) score of dyskinesia was 22 points. When the patient developed dyskinesia, the LD blood concentration had not yet reached the peak, so it was wrong to judge the patient as having peak dyskinesia based on experience in the past. After analysis, it was believed that the reason why dyskinesia occurred when the blood concentration was relatively low was the low LD absorption rate. In order to increase the patient's LD absorption rate, we crushed the drug and dissolved it in water and gave it to the patient orally. Although this method did not change the patient's oral medication dosage and frequency, the dyskinesia was significantly relieved. This case fully illustrates that for PD patients with dyskinesia, the type of dyskinesia may be misjudged based solely on clinical symptoms and experience. It is crucial to use the new electrode prepared by the method of the present invention to detect LD concentration, clarify the cause of dyskinesia, and select an individualized medication regimen.
[0065] Example 2: Changing step (1) of the method of the present invention
[0066] Example 2-1
[0067] Gold and cobalt nanoparticle-anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foams were prepared in a manner similar to Example 1, except that, in step (1), 3 mmol of cobalt nitrate hexahydrate and 3 mmol of dimethylimidazole were added to 30 mL of deionized water; the mixture was stirred for 30 min to obtain a mixed solution.
[0068] Example 2-2
[0069] Gold and cobalt nanoparticle-anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foams were prepared in a manner similar to Example 1, except that in step (1), 0.05 mmol of cobalt nitrate hexahydrate and 0.05 mmol of dimethylimidazole were added to 80 mL of deionized water; the mixture was stirred for 30 min to obtain a mixed solution.
[0070] Example 2-3
[0071] The preparation of gold and cobalt nanoparticle-anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam was carried out in a manner similar to that of Example 1, except that in step (1), a sheet of 2×2 cm 2 The three-dimensional graphene foam subjected to surface oxidation treatment is placed in the mixed solution and maintained at 25° C. for 12 hours.
[0072] Embodiment 2-4
[0073] The preparation of gold and cobalt nanoparticle-anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam was carried out in a manner similar to that of Example 1, except that in step (1), a sheet of 2×2 cm 2 The surface-oxidized three-dimensional graphene foam is placed in the mixed solution and kept at 25° C. for 2 hours.
[0074] Example 3: Modification of step (2) of the method of the present invention
[0075] Example 3-1
[0076] A three-dimensional graphene foam composite material of gold and cobalt nanoparticles anchored nitrogen-doped carbon nanosheet arrays was prepared in a manner similar to that of Example 1, except that in step (2), the ZIF-67 nanosheet array / three-dimensional graphene foam was placed in an alumina ceramic boat and heat treated at 900°C in an argon atmosphere.
[0077] Example 3-2
[0078] A three-dimensional graphene foam composite material of gold and cobalt nanoparticles anchored nitrogen-doped carbon nanosheet arrays was prepared in a manner similar to that of Example 1, except that in step (2), the ZIF-67 nanosheet array / three-dimensional graphene foam was placed in an alumina ceramic boat and heat treated at 300°C in an argon atmosphere.
[0079] Example 3-3
[0080] A three-dimensional graphene foam composite material of gold and cobalt nanoparticles anchored with nitrogen-doped carbon nanosheet arrays was prepared in a manner similar to that of Example 1, except that in step (2), heat treatment was performed in an argon atmosphere for 5 h.
[0081] Embodiment 3-4
[0082] A three-dimensional graphene foam composite material of gold and cobalt nanoparticles anchored with nitrogen-doped carbon nanosheet arrays was prepared in a manner similar to that of Example 1, except that in step (2), heat treatment was performed in an argon atmosphere for 1 h.
[0083] Example 4: Modification of step (3) of the method of the present invention
[0084] Example 4-1
[0085] A three-dimensional graphene foam composite material of gold and cobalt nanoparticles anchored nitrogen-doped carbon nanosheet arrays was prepared in a manner similar to that of Example 1, except that in step (3), 50 μL of a carboxyl-containing gold nanoparticle solution was measured with a pipette and dripped onto the surface of the cobalt nanoparticle-anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam.
[0086] Example 4-2
[0087] A three-dimensional graphene foam composite material of gold and cobalt nanoparticles anchored nitrogen-doped carbon nanosheet arrays was prepared in a manner similar to that of Example 1, except that in step (3), 5 μL of a carboxyl-containing gold nanoparticle solution was measured with a pipette and dripped onto the surface of the cobalt nanoparticle-anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam.
[0088] Example 4-3
[0089] A three-dimensional graphene foam composite material of gold and cobalt nanoparticles anchored nitrogen-doped carbon nanosheet arrays was prepared in a manner similar to that of Example 1, except that in step (3), the self-assembly was carried out at 80° C. for 12 h to obtain gold and cobalt nanoparticles anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam.
[0090] Example 4-4
[0091] A three-dimensional graphene foam composite material of gold and cobalt nanoparticles anchored nitrogen-doped carbon nanosheet arrays was prepared in a manner similar to that of Example 1, except that in step (3), the self-assembly was carried out at 25° C. for 2 h to obtain gold and cobalt nanoparticles anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam.
[0092] The performance of gold and cobalt nanoparticles anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foams prepared by the methods of Examples 2-4 was tested. The test results showed that the performance differences of the composite electrodes of Examples 2-4 were very small, and were all similar to the performance test results of Example 2, such as Figure 4As the LD concentration increases from 0 to 60 μM, the oxidation peak located near 0.15 V increases, as shown in Figure 4 a. The linear fitting curve of peak current and LD concentration is I LD =(4.14±0.92)+(1.32±0.05)C LD (R 2 =0.9930), such as Figure 4 The results show that the composite material synthesized under the conditions of Example 2 has a high sensitivity of 1.32 μA·μM in detecting LD as an electrode material. -1 cm -2 (0-60 μM). The sensitivity of the composite material synthesized under the conditions of Examples 3 and 4 as an electrode material for detecting LD is similar to this.
[0093] The gold and cobalt nanoparticles anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam composite electrode of the present invention is used for patients, and the LD blood concentration is detected by an electrochemical method, so as to achieve accurate treatment of PD patients and avoid the occurrence of dyskinesia. Here is a clinical example for explanation: Basic information of the patient: male, 65 years old, weight 67kg, diagnosed with PD 15 years ago due to bradykinesia and right limb tremor, education level: high school, MMSE score: 27 points, UPDRS opening score: Part III 14 points, Part IV 11 points, Hoehn-Yahr stage: 3, medication status: After the diagnosis of PD, the initial oral administration of Madopar (each tablet contains 200 mg of levodopa and 50 mg of benserazide) had a good therapeutic effect (the specific dosage is unknown). Five years ago, the patient felt that the duration of the drug effect was shortened, and involuntary twisting of the neck and limbs occurred after taking the medicine, and dyskinesia was diagnosed. At present, the patient takes 0.75 tablets of Madopar orally each time, 4 times a day. The patient felt that dyskinesia occurred more than 1 hour after oral medication, and lasted for about 1 hour to relieve. Before detecting the LD concentration, according to the time of dyskinesia and the time of oral medication, the patient was considered to have peak dyskinesia, and tried to reduce the dosage each time or increase the interval between medications, but the dyskinesia did not improve significantly. The patient was tested for LD blood concentration by electrochemical method using the new electrode material of the gold and cobalt nanoparticle anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam composite material of the present invention, which showed that the LD blood concentration reached a peak about 2 hours after taking the medication. The patient developed dyskinesia half an hour after oral medication, and the UDysRS (16-26 items) score of dyskinesia was 22 points. When the patient developed dyskinesia, the LD blood concentration had not yet reached the peak, so it was wrong to judge the patient as having peak dyskinesia based on experience in the past. After analysis, it was believed that the reason why dyskinesia occurred when the blood concentration was relatively low was the low LD absorption rate. In order to increase the patient's LD absorption rate, we crushed the drug and dissolved it in water and gave it to the patient orally. Although this method did not change the patient's oral medication dosage and frequency, the dyskinesia was significantly relieved. This case fully illustrates that for PD patients with dyskinesia, the type of dyskinesia can be misjudged based solely on clinical symptoms and experience. It is crucial to use the new electrode prepared in this project to detect LD concentration, clarify the cause of dyskinesia, and choose an individualized medication plan.
[0094] Comparative Example 1
[0095] (1) Preparation of ZIF-67 nanosheet arrays / 3D graphene foam by room temperature synthesis
[0096] 10 mmol of cobalt nitrate hexahydrate and 10 mmol of dimethylimidazole were added to 100 mL of deionized water; stirred for 30 min to obtain a mixed solution; then a piece of 2×2 cm 2The surface-oxidized three-dimensional graphene foam is placed in the mixed solution and kept at 25° C. for 6 hours; the obtained product is washed with deionized water for several times and dried to obtain ZIF-67 nanosheet array / three-dimensional graphene foam;
[0097] (2) Preparation of cobalt nanoparticle-anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam by high-temperature calcination
[0098] The ZIF-67 nanosheet array / three-dimensional graphene foam was placed in an alumina ceramic boat and heat treated at 700° C. in an argon atmosphere for 2 h. The mixture was then cooled to room temperature to obtain cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam.
[0099] (3) Preparation of gold and cobalt nanoparticle-anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam by self-assembly
[0100] 10 μL of a carboxyl-containing gold nanoparticle solution was measured with a pipette and dropped onto the surface of the cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam, and then kept at 25° C. for 4 h for self-assembly to obtain gold and cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam.
[0101] The gold and cobalt nanoparticles anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam composite material prepared in Comparative Example 1 was subjected to scanning morphology observation. Figure 5 As shown, a large block structure was formed, and no uniform nanosheet array structure was formed.
[0102] The performance of the gold and cobalt nanoparticles anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam prepared by the method of Comparative Example 1 was tested, and the results are as follows: Figure 6 As the LD concentration increases from 0 to 60 μM, the oxidation peak located near 0.12 V increases, as shown in Figure 6 a. The linear fitting curve of peak current and LD concentration is I LD =(2.72±0.48)+(0.21±0.02)C LD (R 2 =0.9636), such as Figure 6 The results show that the composite material synthesized under these conditions has a low sensitivity of 0.21 μA·μM in detecting LD as an electrode material. -1 cm -2 (0~60μM).
[0103] The gold and cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam composite electrode of the present invention was used on patients, and the LD blood concentration was detected by an electrochemical method. The LD blood concentration did not respond within 0.5-2 hours after taking the medicine. The reason is that the synthesis conditions of Comparative Example 1 lead to a decrease in the conductivity of the electrode, affecting the high sensitivity.
[0104] Comparative Example 2
[0105] (1) Preparation of ZIF-67 nanosheet arrays / 3D graphene foam by room temperature synthesis
[0106] 2mmol of cobalt nitrate hexahydrate and 2mmol of dimethylimidazole were added to 80mL of deionized water; stirred for 30min to obtain a mixed solution; then a piece of 2×2cm 2 The surface-oxidized three-dimensional graphene foam is placed in the mixed solution and kept at 25° C. for 6 hours; the obtained product is washed with deionized water for several times and dried to obtain ZIF-67 nanosheet array / three-dimensional graphene foam;
[0107] (2) Preparation of cobalt nanoparticle-anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam by high-temperature calcination
[0108] The ZIF-67 nanosheet array / three-dimensional graphene foam was placed in an alumina ceramic boat and heat treated at 1000° C. in an argon atmosphere for 8 h, and then cooled to room temperature to obtain cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam.
[0109] (3) Preparation of gold and cobalt nanoparticle-anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam by self-assembly
[0110] 10 μL of a carboxyl-containing gold nanoparticle solution was measured with a pipette and dropped onto the surface of the cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam, and then kept at 25° C. for 4 h for self-assembly to obtain gold and cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam.
[0111] The gold and cobalt nanoparticles anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam composite material prepared in Comparative Example 2 was subjected to scanning morphological observation. Figure 7 As shown, a thicker structure is formed and the distance between nanosheets decreases.
[0112] The performance of the gold and cobalt nanoparticles anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam prepared by the method of Comparative Example 2 was tested, and the results are as follows: Figure 8 As the LD concentration increases from 0 to 60 μM, the oxidation peak located near 0.13 V increases, as shown in Figure 8a. The linear fitting curve of peak current and LD concentration is I LD =(2.32±0.61)+(0.35±0.05)C LD (R 2 =0.9834), such as Figure 8 The results show that the composite material synthesized under the conditions of comparative example 2 has a low sensitivity of 0.35 μA·μM in detecting LD as an electrode material. -1 cm -2 (0~60μM).
[0113] The gold and cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam composite electrode of the present invention was used on patients, and the LD blood concentration was detected by an electrochemical method. The LD blood concentration had a very small current response within 0.5-2 hours of taking the medicine. The reason is that the synthesis conditions of Comparative Example 2 lead to a decrease in the conductivity of the electrode, affecting the high sensitivity.
[0114] Comparative Example 3
[0115] (1) Preparation of ZIF-67 nanosheet arrays / 3D graphene foam by room temperature synthesis
[0116] 2mmol of cobalt nitrate hexahydrate and 2mmol of dimethylimidazole were added to 80mL of deionized water; stirred for 30min to obtain a mixed solution; then a piece of 2×2cm 2 The surface-oxidized three-dimensional graphene foam is placed in the mixed solution and kept at 25° C. for 6 hours; the obtained product is washed with deionized water for several times and dried to obtain ZIF-67 nanosheet array / three-dimensional graphene foam;
[0117] (2) Preparation of cobalt nanoparticle-anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam by high-temperature calcination
[0118] The ZIF-67 nanosheet array / three-dimensional graphene foam was placed in an alumina ceramic boat and heat treated at 500° C. in an argon atmosphere for 2 h. The mixture was then cooled to room temperature to obtain cobalt nanoparticle-anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam.
[0119] (3) Preparation of gold and cobalt nanoparticle-anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam by self-assembly
[0120] 100 μL of the gold nanoparticle solution with carboxyl group was measured with a pipette and dropped onto the surface of the cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam, and then kept at 120° C. for 24 h for self-assembly to obtain gold and cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam.
[0121] The gold and cobalt nanoparticles anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam composite material prepared in Comparative Example 3 was subjected to scanning morphological observation. Fig. 9 As shown, the thickness of the nanosheets becomes thinner, but nanosheets with greater dispersion and unevenness are formed.
[0122] The performance of the gold and cobalt nanoparticles anchored nitrogen-doped carbon nanosheets / three-dimensional graphene foam prepared by the method of Comparative Example 3 was tested, and the results are as follows: Fig.10 As the LD concentration increases from 0 to 60 μM, the oxidation peak located near 0.13 V increases, as shown in Fig.10 a. The linear fitting curve of peak current and LD concentration is I LD =(2.02±0.45)+(0.74±0.06)C LD (R 2 =0.9686), such as Fig.10 The results show that the composite material synthesized under these conditions has a low sensitivity of 0.74 μA·μM in detecting LD as an electrode material. -1 cm -2 (0~60μM).
[0123] The gold and cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam composite electrode of the present invention was used on patients, and the LD blood concentration was detected by an electrochemical method. The current response of the LD blood concentration was limited within 0.5-2 hours after taking the medicine. The reason is that the synthesis conditions of Comparative Example 3 lead to a decrease in the conductivity of the electrode, affecting the high sensitivity.
Claims
1. A method for preparing a three-dimensional graphene foam composite material of gold and cobalt nanoparticles anchored with nitrogen-doped carbon nanosheet arrays, characterized in that: The following steps are involved: (1) placing the surface-oxidized three-dimensional graphene foam in a mixed solution of cobalt nitrate hexahydrate and dimethylimidazole and keeping it at room temperature for 2 h to 12 h; washing the obtained product with deionized water and drying it to obtain dimethylimidazole cobalt nanosheet array / three-dimensional graphene foam; The size of the three-dimensional graphene foam is 2×2 cm 2 , and in the mixed solution, the concentration of cobalt nitrate hexahydrate is 0.0006mol / L-0.1mol / L, and the concentration of dimethylimidazole is 0.0006mol / L-0.1mol / L; (2) heat treating the dimethylimidazole cobalt nanosheet array / three-dimensional graphene foam at 300° C.-900° C. in an argon atmosphere for 1 h-5 h; and then cooling to room temperature to obtain cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam; (3) 5 μL-50 μL of a carboxyl-containing gold nanoparticle solution is added dropwise onto the surface of the cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam, and then maintained at 25° C.-80° C. for 2 h-12 h for self-assembly to obtain gold and cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam.
2. The preparation method according to claim 1, characterized in that: In step (1), the three-dimensional graphene foam subjected to surface oxidation treatment is placed in a mixed solution of cobalt nitrate hexahydrate and dimethylimidazole and maintained at room temperature for 3 h to 9 h; in step (1), in the mixed solution, the concentration of cobalt nitrate hexahydrate is 0.001 mol / L to 0.05 mol / L, and the concentration of dimethylimidazole is 0.001 mol / L to 0.05 mol / L.
3. The preparation method according to claim 1, characterized in that: In step (2), the cobalt dimethylimidazole nanosheet array / three-dimensional graphene foam is heat treated at 500° C.-800° C. in an argon atmosphere for 1 h-3 h.
4. The preparation method according to claim 1, characterized in that: In step (3), 5 μL-30 μL of a carboxyl-containing gold nanoparticle solution is measured and added dropwise to the surface of the cobalt nanoparticle-anchored nitrogen-doped carbon nanosheet / three-dimensional graphene foam, and then maintained at a temperature of 25° C.-50° C. for 2 h-8 h for self-assembly.
5. A three-dimensional graphene foam composite material of gold and cobalt nanoparticles anchored with nitrogen-doped carbon nanosheet arrays prepared according to the method of any one of claims 1 to 4, characterized in that: The composite material consists of C, N, Co, Au and O elements and has a morphology in which a triangular dimethylimidazole cobalt nanosheet array is uniformly grown on oxidized three-dimensional graphene foam.
6. Use of the three-dimensional graphene foam composite material of gold and cobalt nanoparticles anchored with nitrogen-doped carbon nanosheet arrays according to claim 5 prepared by the method according to any one of claims 1 to 4 as an electrode material.
7. The use according to claim 6, characterized in that The composite material is used as an electrode for detecting the concentration of levodopa.
8. The use according to claim 7, characterized in that The composite material is used as an electrode to detect the blood concentration of levodopa.
9. The use according to claim 7, characterized in that: The composite material is used as an electrode to form an electrochemical detection instrument for detecting the blood concentration of levodopa.